Qisas Punishment Imposed by Surambi Court in Kasunanan of Surakarta Post Palihan Nagari - Kasiran, Sugiarti; D. Dienaputra, Reiza; Nugraha, Awaludin; Kartika, N. (Al-Daulah: Jurnal Hukum dan Perundangan Islam, 2021)
Surambi Court began in the time of Sunan Paku Buwono IV ruling in 1788-1820 M. Surambi as the highest court was authorized to pass judgments over serious crimes, including murder cases in Surakarta. Back in the time, soldiers assigned to executing the punishment were established: Nirbaya, Martalulut, and Singanagara. Surakarta was the region under the Dutch colonialism, and this situation did not allow Islamic Law to be fully enforced in the region due to the interference of the invaders. This research employed historical legal approach intended to study the legal history from the perspective of the development and the origin of legal system growing in a certain society and to compare it to another different law. The research methods involved the studies of history such as heuristic, critical, interpretational, and historiographic approaches.  The research found out that qisas punishment was not imposed as what is governed in Islamic Law. The Dutch interference in internal issues in the keraton (palace) took over all court decisions under its control. The Dutch could aggravate or even alleviate punishment imposed on a defendant as long as it benefitted the Dutch.